The poetry of Guy Butler - Van der Mescht, Hennie (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1981)
This study of ButIer's poetry proceeds chronologically in accordance with the dates of composition of his poems. The first task has, therefore, been the compilation of a chronology of his poems. Butler rarely dates his poems; nor does he keep a diary. Yet there are several criteria which make sensible dating of his poems possible. The first is the date of publication of individual poems. Many of the poems which appear in one or more of the five collections were published earlier in army magazines, student newspapers, and the like. A work which can be traced back to one of these early sources may be assumed to have been written fairly soon before its date of publication. Another criterion is subject. It is possible to discern periods in the poet's career in relation to the subjects of his poems. The most obvious example is the War Period. Allied to subject is the criterion of theme. To use the War Period again, poems written during or immediately after the war years all treat the theme of man's dehumanisation. Both subject and theme are linked with biography. It is often possible to ascertain Butler's location from details in the poem; knowledge of his movements thus enables one to date such a poem. Butler's style is the most significant criteion. This study is based on the observation that his style develops as time passes. The Butler of the Sixties is different from the Butler of the Fifties as far as style of writing is concerned. A poem which defies dating on all other grounds cannot escape this ultimate test. Each of these criteria - date of publication, subject matter and theme linked to biography, and style - has limited reliability as a guide to dating the poems. But combined they are a meaningful instrument to assist in the structuring of a chronology whose most valuable source was the poet himself who was kind enough to search his memory for dates. The fact that Butler rewrote or revised a number of his poems several times does of course raise the question: Is the first version merely a stage in the development of the poem, or a poem in its own right? This study is based on the opinion that a poem is a poem, regardless of the number of versions which precede or follow it, provided it is a complete statement. Each version should, in fact, be regarded as representative of the poet's thoughts, feelings, and skills at the time he wrote it, and is lndependent of subsequent versions. For the purposes of this chronology, poems have been placed at the time of the experience from which they grew. This thesis does, however , take cognizance of the ehanges in style or theme later versions may reveal.
Keywords: Butler, Guy, 1918-2001 -- Criticism and interpretation; South African poetry (English)